Answer:
A. (U+V)^2 or (U-V)^2
Step-by-step explanation:
Answer:
1.2
Step-by-step explanation:
9/5*2/3=1.2
(8x 2 −15x)−(x 2 −27x)=ax 2 +bxleft parenthesis, 8, x, squared, minus, 15, x, right parenthesis, minus, left parenthesis, x, squ
quester [9]
Answer:
<h2>5</h2>
Step-by-step explanation:
Given the expression (8x² −15x)−(x² −27x) = ax² +bx, we are to determine the value of b-a. Before we determine the vwlue of b-a, we need to first calculate for the value of a and b from the given expression.
On expanding the left hand side of the expression we have;
= (8x² −15x)−(x² −27x)
Open the paranthesis
= 8x² −15x−x²+27x
collect the like terms
= 8x²−x²+27x −15x
= 7x²+12x
Comparing the resulting expression with ax²+bx
7x²+12x = ax²+bx
7x² = ax²
a = 7
Also;
12x = bx
b =12
The value of b - a = 12 - 7
b -a = 5
Hence the value of b-a is equivalent to 5
Answer:
1) Divide the numerator by the denominator.
2) Write down the whole number result.
3) Use the remainder as the new numerator over the denominator. This is the fraction part of the mixed number.
Step-by-step explanation:
not sure of this will help... but hope it does!
Answer:
10 + 5
Step-by-step explanation:
If you are subtracting a negative then it become adding a positive. A way to remember this is because it has matching socks.